Residential Heritage of Nova Friburgo The rescue of memory from workers’ village - Holzer, Werther; Fernandes, Marina Pires (Technical and Scientific Journal Green Cities, 2021)
This work aims to rescue the memory and culture of the population of Friburgo through the view of the landscape under the residential heritage of Nova Friburgo, RJ. Given the vulnerability of architectural heritage regarding the renovation process, attributed to the city's development and the diversity of architecture given its Swiss and German colonization, and later added other nationalities, the heritage of the city is diversified and present, but poorly preserved. Based on the concepts of landscape approached by Augustin Berque and Pierce Lewis, we start from the perspective that residential heritage comprises the basis of the population's daily life and that, through looking at these buildings from the definition of landscape-mark and landscape-matrix and the axioms, of the respective authors, it is understood the processes of relationship between the population and the city, in addition to their study and formation, and an approach is created for the preservation of these properties. It seeks to bring to the surface, through housing, the meaning of heritage, as something that has been preserved, not only for aesthetic issues but mainly for its immaterial value. For this, we sought to create a material that presents these buildings using the landscape guides presented by Lewis, instigating a critical sense and analysis about them, from a catalog of assets, focusing on workers' villages, arranged through an interactive map, which presents the georeferenced properties, seeking to fill the information gap in a clear and accessible way.KEYWORDS: Residential Heritage. Landscape Theory. Heritage Education.